Variables that predict academic achievement in the spanish compulsory secondary educational system: a longitudinal, multi-level analysis - Martín, Elena; Martínez-arias, Rosario; Marchesi, Alvaro; Pérez, Eva M. (The Spanish Journal of Psychology, 2008)
This article presents a study whose objective was to identify certain personal and institutional variables that are associated with academic achievement among Spanish, secondary school students, and to analyze their influence on the progress of those students over the course of that stage of their education. In order to do this, a longitudinal, multi-level study was conducted in which a total of 965 students and 27 different schools were evaluated in Language, Math and Social Science at three different times (beginning, middle and end of the period). The results show progress in all the schools and in all areas. As for the personal, student variables, the longitudinal, HLM analyses confirmed the importance of sex and sociocultural background and, distinguishing it from other studies, also the predictive capacity of meta-cognitive abilities and learning strategies on success in school. On the institutional level, the school climate and teachers’ expectations of their students were the most relevant of the variables studied. The size of the school, the percentage of students who repeat grades, and the leadership of the administration also explained a portion of the variance in some areas.